Continuous flow Aza-Michael reaction for preparing the fast-acting synthetic opioid drug Remifentanil - Artur de Lara Lima Vaz; João Luis Callegari Lopes; Giuliano Cesar Clososki (Universidade de São Paulo, 2023)
Abstract Remifentanil is a modern fentanyl analogue with ultrashort-action granted by an esterase-labile methyl propanoate chain. Here, we present the development of a continuous flow methodology for the key N-alkylation step of remifentanil preparation in a biphasic, "slug-flow" regime. We screened parameters under microwave-assisted reactions, translated conditions to flow settings, and obtained remifentanil under 15-min residence time in a 1-mL microreactor, with a space-time yield of 89 mg/mL·h and 94% yield.